El cuento como estrategia didáctica para mejorar la comunicación escrita en los estudiantes de octavo grado de educación general básica de la unidad educativa Lauro Damerval Ayora Nº1 de la ciudad de Loja. Período académico 2015-2016 - Vera Ordóñez, María Alexandra (2016)
The research work entitled; THE TALE AS A STRATEGY TEACHING TO IMPROVE THE COMMUNICATION WRITTEN IN EIGHTH-GRADERS BASIC GENERAL EDUCATION EDUCATIONAL UNIT LAURO DAMERVAL AYORA N ° 1 OF THE CITY OF LOJA. ACADEMIC PERIOD 2015-2016, It was proposed as a general objective; analyze the story as a teaching strategy to encourage creativity in eighth-graders Basic General education of the institution being investigated. The methods used to conduct the research were the following: the scientist, inductivo- deductivo, analitico¬-synthetic and descriptive. The techniques that were applied were: the bibliographic, the survey and the structured interview. As instrument applied the questionnaire and structured interview guide. Among the most significant results, were evidence that the story as a teaching strategy has an impact on the development of creativity, allowing the student imagine, fantasize and recreate new fictitious situations that help encourage creativity, so it is concluded that the teachers in the educational unit Lauro Damerval Ayora N ° 1, they used the story as a teaching strategy only sporadically to stimulate the creative capacity of students, so it is recommended to teachers of language and literature used most frequently to the story as a teaching strategy writing and narrating stories with different titles, characters and outcomes from the way oral and written; which will develop written communication skills and encourage creativity in students